Unveiling the Nuances of Human Interaction within Organizational Settings - Sulastri, Rani (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: The primary purpose of this research is to explore the intricate dynamics of human interaction in organizational contexts, focusing on communication, teamwork, leadership, and organizational culture. By comprehensively examining these aspects, the study seeks to uncover how they collectively impact organizational effectiveness and individual satisfaction. Research Design and Methodology: The methodology involves a qualitative literature review, integrating data from various academic sources, including journals and books. The research utilizes systematic search strategies, rigorous inclusion and exclusion criteria, and qualitative content analysis to ensure a comprehensive synthesis. Findings and Discussion: The study reveals that effective communication is pivotal in maintaining operational efficiency and fostering a positive work environment. Leadership styles significantly influence workplace dynamics, affecting everything from decision-making processes to employee morale. Teamwork and organizational culture are identified as crucial elements that contribute to the overall health and productivity of organizations. Implications: The findings suggest practical applications for organizational leaders aiming to enhance workplace interactions and organizational policies. Recommendations include investing in leadership development, fostering a collaborative culture, and implementing robust communication systems to improve engagement and productivity. Theoretical contributions include a deeper understanding of the interplay between individual behaviors and organizational structures, offering a foundation for future research in organizational behavior.